Bloodless, painless, suture less circumcision: A combination of diode laser with cyanoacrylate skin glue in patient with second grade of phimosis - Amsriza, Fadli Robby; Fakhriani, Rizka (Institute of Computer Science (IOCS), 2025)
Circumcision is a common surgical operation that entails excising the foreskin from the penis, primarily to improve hygiene and prevent the accumulation of smegma. This practice is widely observed worldwide, especially within Muslim and Jewish populations. However, despite its advantages, circumcision may lead to several complications, such as excessive bleeding and infections. A healthy 13-year-old male presented for circumcision due to grade 2 phimosis, seeking to improve his personal hygiene. The procedure was executed using a combination of diode laser technology and cyanoacrylate skin glue, which minimized tissue trauma and provided effective wound closure. When circumcision is performed utilizing advanced methods such as diode laser and cyanoacrylate glue, it is regarded as a safe and effective intervention. This approach offers considerable benefits in terms of recovery duration, cosmetic results, and overall patient comfort, while also maintaining low rates of complications.